2006
DOI: 10.1002/elan.200603540
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Film Electrode for the Cathodic Electrochemical Determination of Thiamethoxam

Abstract: A cathodic electrochemical application of bismuth film modified glassy carbon electrode was investigated with the objective of determining thiamethoxam insecticide. The conditions of bismuth film deposition (electrode pretreatment procedure, composition of the plating solution, plating potential and film stability) were optimized using electrochemical and microscopic techniques. It was found that the bismuth film generation on glassy carbon substrate in a plating solution of 0.02 M Bi(NO 3 ) 3 , 1 M HCl and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 30 publications
4
60
0
8
Order By: Relevance
“…The application of BiEs to medical samples has included monitoring the release of zinc from pancreatic islets [43], the determination of cobalt and nickel in aqueous humor (from the human eye) and cerebrospinal fluid [85], the analysis of blood samples [24,41,133] and the analysis of urine [23,38,87]. Great diversity exists in the use of BiEs for the determination of heavy metals in food samples including wine and fruit juice [28,37,74,139,150,169,188], various vegetable samples (potato and maize [77], sugar cane [142], garlic [144], cabbage, lettuce and celery [160]), meat samples (sausage, tuna and sardines [186]) and other samples including tomato sauce [28], tea leaves [64,116] and tobacco [33]. While various natural and marine water samples make up the bulk of environmental samples, BiEs have also been applied to complex sewage samples [128,181], plant extracts [75,86], fertilizer samples [103,145] and a number of soil samples [33,34,39,49,55,104,141].…”
Section: Real Analytical Applications Of Biesmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of BiEs to medical samples has included monitoring the release of zinc from pancreatic islets [43], the determination of cobalt and nickel in aqueous humor (from the human eye) and cerebrospinal fluid [85], the analysis of blood samples [24,41,133] and the analysis of urine [23,38,87]. Great diversity exists in the use of BiEs for the determination of heavy metals in food samples including wine and fruit juice [28,37,74,139,150,169,188], various vegetable samples (potato and maize [77], sugar cane [142], garlic [144], cabbage, lettuce and celery [160]), meat samples (sausage, tuna and sardines [186]) and other samples including tomato sauce [28], tea leaves [64,116] and tobacco [33]. While various natural and marine water samples make up the bulk of environmental samples, BiEs have also been applied to complex sewage samples [128,181], plant extracts [75,86], fertilizer samples [103,145] and a number of soil samples [33,34,39,49,55,104,141].…”
Section: Real Analytical Applications Of Biesmentioning
confidence: 99%
“…The individual contributions came from "traditional" propagators of bismuth electrodes from the U.S.A. [71,83], Slovenia [72,85,89], Czech Republic [72,90,96], Poland [78], Greece [72,73,82,87,90], Portugal [75], France [86,92] and the UK [94]; however, the sixth year of contemporary era of electroanalysis with BiEs was also the sign of new research groups appearing over the whole world. Thus, the aboveintroduced "Bismuth Club" -a hypothetical association and so-far unrealized idea of some pioneers in the field -could invite further members from Europe (Germany [70,93], Spain [80], Italy [91], and Serbia [77]), North America (Delaware, USA [76]), and the Far East (China [79,84], Thailand [76]), and Australia [74,81]. Such diversity of the scientific teams involved in the intensive research on BiEs and BiFEs was naturally mirrored in the respective activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Cathodic stripping voltammetric determination of As(III), Te(IV), Sb(III and V) and Se(IV) using in situ plated BiFEs has been reported.…”
Section: -12mentioning
confidence: 99%
“…By using of an "environmentally friendly" electrode material -bismuth (mostly as electrodeposited bismuth film as it is well known resemblance in electrochemical behavior between Bi and Hg) in electrochemical "stripping" analysis, [20,21,22] it is possible to overcome issues related to mercury based materials. Although conventional and micro bismuth film electrodes have been widely used in electrochemical analysis of various organic compounds [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] their relevance for folic acid determination has been very poorly exploited. Only Ananthi et al [38] reported determination of folic acid using glassy carbon electrode modified with an electrodeposited bismuth nanowires by square wave voltammetry.…”
Section: Introductionmentioning
confidence: 99%